Association between the triglyceride-glucose index and symptomatic intracranial atherosclerotic stenosis in nondiabetic patients: a retrospective study - Yang Yang; Chunhao Mei; Xiaoning Guo; Bojun Han; Qingguang Wang (BMC Neurology)
Abstract Objective To investigate the relationship between the triglyceride-glucose (TyG) index and symptomatic intracranial atherosclerotic stenosis (sICAS) in non-diabetic patients. Methods This retrospective study analyzed 968 nondiabetic acute ischemic stroke (AIS) patients admitted between January 2022 and December 2024. Intergroup differences between the sICAS group and the non-sICAS group were analyzed. The TyG index was calculated, and stratified into TyG tertiles (T1–T3). Multivariable logistic regression models adjusted for age, sex, smoking status, alcohol use, hypertension status, BMI, and lipid profiles were used to assess associations with sICAS, stenosis severity, and plaque vulnerability. Restricted cubic splines explore nonlinear relationships. Results Among the 968 included patients, the median age was 58 (IQR 50–66) years, and 43.39% were male. The median TyG index was 8.96 (IQR 8.77, 9.13). Patients with sICAS presented significantly higher total cholesterol (TC) levels and TyG index values, and lower high-density lipoprotein (HDL) levels. The high-TyG group presented a significantly greater prevalence of male, sex, a history of smoking and hypertension, an elevated body mass index (BMI), and lower HDL levels. An elevated TyG index was significantly associated with sICAS, moderate and severe stenosis and vulnerable plaques. This association was maintained after adjusting for age, sex, smoking, alcohol use, hypertension, BMI, TC, HDL, and low-density lipoprotein (LDL) levels. Multivariable-adjusted spline regression models revealed that a progressively increasing risk of sICAS, moderate and severe stenosis and vulnerable plaques was related to an elevated TyG index. Conclusion An elevated TyG index is significantly associated with sICAS and independently associated with severe intracranial arterial stenosis and vulnerable plaques in nondiabetic AIS patients.